Development and Validation of New Stability Indicating HPLC Method for the Quantitative Determination of Topiroxostat in Bulk and Dosage Form (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Topiroxostat is a novel xanthine oxidoreductase (XOR) inhibitor; used to treat hyperuricemia and gout. The system comprised; column of Agilent Zorbax Bonus RP C18 (250×4.6) mm, 5µ and mobile phase containing 50 mill molar potassium dihydrogen phosphate, which had a pH of 3.3 (adjusted by 5% OPA) and ACN, in 20:80, v/v ratio. The mobile phase was pumped through the column at a temperature of 30°C and a flow rate kept at 1 ml/min. Topiroxostat had retention time of 6.99 minutes, at 272 nm. According to the ICH guidelines, the developed approach has undergone statistical validation. The calibration curve was linear from 0.01-120 µg/mL with excellent R2=1. Analytical limits were 0.075 µg/mL for detection and 0.229 µg/mL for quantitation respectively. This newly developed approach exhibited high accuracy and reproducibility with RSD less than 2. Five different stress conditions were applied to assess Topiroxostat stability. Forced degradation studies revealed significant degradation upon exposure to alkaline stress (12.33%), photolytic stress (14.44%), and oxidative stress (30.30%) but little degradation was observed in remaining applied stress conditions. Thus, the developed stability-indicating approach can be used for the estimation of Topiroxostat in API and pharmaceutical formulations.